Development of an Ionic Liquid Based Method for the Preparation of Albumin Nanoparticles. Issue 34 (13th September 2018) - Demirkurt, Begüm; Akdogan, Yasar
Abstract: Albumin based nanocarriers have been widely used in drug delivery studies. Here, we developed a water‐in‐ionic liquid (IL) emulsion‐like method to prepare bovine serum albumin (BSA) nanoparticles as alternative to the traditional organic solvents containing techniques. Conformational changes of albumin induced by the imidazolium based ILs at the water‐IL interface triggers the BSA nanoparticle formation. The albumin nanoparticle formation are dependent on the experimental parameters and the hydophobicity of the IL. At pH 9.0, using 1.3%wt of BSA in water/1‐butyl‐3‐methyl imidazolium tetrafluoroborate (BmimBF4 ) (50/50 mol%) and TX‐100/butanol surfactant mixture yields uniformly distributed 200 nm average sized BSA nanoparticles. Different than BmimBF4, using a more hydrophilic IL, EmimBF4 yielded albumin aggregates. Instead, using a more hydrophobic IL, HmimBF4 produced albumin nanoparticles but a non‐uniform size distribution was obtained. These results indicate that the ionic liquids called green and designer solvents can be also used to synthesize albumin nanoparticles. Abstract : Albumin nanocarriers have been widely used in drug delivery studies. As alternative to the other synthesis techniques, herein an ionic liquid based emulsion‐like technique was developed to synthesize albumin nanoparticles. By using an ionic liquid (BmimBF4 ) ‐ water binary system, uniformly distributed 200 nm average sized albumin nanoparticles were obtained.